Nutrient Removal of Pulp Wastewater using Bench Scale Extended Aeration Activated Sludge Treatment - Mohd Fauzi, Muhammad Adli Hakim (Universiti Teknologi PETRONAS, 2021)
A factory in Kedah, Malaysia producing biodegradable food packaging is utilizing rice straws and rice husks in order to tackle the increasing amount of plastic wastage. Currently, the factory is using chemical treatment to treat their pulp wastewater before releasing it back to the river. Objective of this study is to determine the feasibility of treating the pulp wastewater using bench scale activated sludge treatment system at 20% organic loading, diluted with domestic wastewater of an average 500 mg/L chemical oxygen demand concentration. A bench scale Extended Aeration Activated Sludge treatment system was set up using a reactor consist of an aeration tank with 4000 to 6000 mg/L initial biomass and a clarifier chamber for the biomass to settle. A 20 L influent tank with mixer was used to feed the wastewater into the reactor with flow rate of 2.6 L per day. Influent and effluent samples were monitored for Nitrate, Ammonia and Total Phosphorus concentrations.